The phenomenon of “the death of the Author” in European postmodernspace as a sign of transitionalcultural processes at the end of the 20th century - Liva, Natalya (Scientific herald of Tchaikovsky National Music Academy of Ukraine, 2018)
Relevance of the study. The problem of cultural genesis of postmodern phenomenon of “the death of the Author” has been regarded in the article. The phenomenon has given birth to identical things that independently and simultaneously emerged in literature and music in the second half of the 20th century. There has been little research done on the problem. The phenomenon of “the death of the Author” was initially analyzed and defined by R. Barthes and M. Foucault as that of entirely literary origin. But it also finds its specifically musical embodiment in the composition technique of minimal music and in the phenomenon of polystylistic, discovered by A. Schnittke. These analogies might not be characterized as deliberate extrapolation because of the absence of any apparent artistic interactions and of obvious synchronicity of emergence of the phenomena in question. The main objective of the study is, having analyzed the principal cultural tendencies at the turn of the 20th – 21st centuries, to prove and to demonstrate the link of literary and musical representations of the phenomenon of “the death of the Author” with large-scale processes of the new understanding of the image of the world and human’s place in the Universe. Methodology of the study. The search of the general cultural genesis of literary and musical embodiments of the phenomenon of “the death of the Author” was done by intensive use of the hermeneutic method as a tool for the interpretation of artistic (that is, literary and musical) texts as key sense-bearing components of the European culture as a semantic whole. The method of historical analysis also became a necessary research instrument since it made possible retrospective explanation of cultural processes of the second half of the 20th century. The comparative method helped to identify certain literary and musical phenomena as similar things. Results and conclusions. The hermeneutic, historical and comparative analysis of the phenomenon of “the death of the Author” as an indicator of transitional processes in the European mentality produces paradoxical results: it emphasizes positive semantics of the phenomenon contrary to obviously pessimistic semantics of the term-metaphor itself. The post-modern phenomenon of “the death of the Author” fulfils a special compensatory mission in the art that lies in the shift of the accent from excessive concentration of the artist on his own person to the new understanding of himself as an important, but comparatively humble particle of the gigantic Universe.